Left ventricular outflow tract obstruction in hypertrophic cardiomyopathy and the impact of mavacamten. (November 2022) - Mathai, Susan; Williams, Lynne
Hypertrophic cardiomyopathy (HCM) is a common genetic disorder characterised by unexplained left ventricular hypertrophy. Left ventricular outflow tract obstruction is an integral component of the disease, often resulting in significant symptoms, but also carrying a risk of progression to heart failure and death. Advancements in our understanding of the pathophysiology of HCM have led to the development of new therapies targeting the molecular basis of the disease at the level of the cardiac sarcomere, the basic contractile apparatus of the myocardium. Myosin modulators are a novel class of small molecules which target cardiac myosins directly to modulate cardiac contractility. The myosin inhibitors present the first advancement in pharmacological management of obstructive HCM in almost 35 years, with a growing body of evidence for the safety, tolerability and efficacy of mavacamten, and to a lesser extent aficamten. The aim of this review is to summarise the current management of patients with obstructive HCM and review the most recent available data from clinical trials pertaining to myosin inhibition.